Insurrection days looking for the sublime: the punk scenes of Portugal and Brazil - Guerra, Paula (2019)
This article focuses on the presentation, explanation and understanding of representations about aesthetic, artistic and experiential authenticity, by actors of Portuguese and Brazilian punk scenes, between the years of 1977 and 2016. It is based on the sociological principle that the reflective knowledge of social actors is essential for scientific reconstruction and, as such, for advancement in social theory. Based on a reflexive methodology, three specific objectives are examined: to problematize the complex relations between ethos, aesthetics and do-it-yourself (DIY)praxis and the establishment of punk and its (sub)scenes in societies outside the gravitational axis of Anglo-Saxon hegemony ; identify the set of activities, skills and abilities in the punk spectrum which constitute an ethos and a praxis of authenticity and, finally, elucidate, in Weberian terms, the many contradictory meanings that the actors attribute to punk and their respective experiences of style and ideology.